Functional Divergence Drives Invasibility of Plant Communities at the Edges of a Resource Availability Gradient - Enrico Tordoni; Francesco Petruzzellis; Andrea Nardini; Giovanni Bacaro (Diversity, 2020)
Invasive Alien Species (IAS) are a serious threat to biodiversity, severely affecting natural habitats and species assemblages. However, no consistent empirical evidence emerged on which functional traits or trait combination may foster community invasibility. Novel insights on the functional features promoting community invasibility may arise from the use of mechanistic traits, like those associated with drought resistance, which have been seldom included in trait-based studies. Here, we tested for the functional strategies of native and invasive assemblage (i.e., environmental filtering hypothesis vs. niche divergence), and we assessed how the functional space determined by native species could influence community invasibility at the edges of a resource availability gradient. Our results showed that invasive species pools need to have a certain degree of differentiation in order to persist in highly invaded communities, suggesting that functional niche divergence may foster community invasibility. In addition, resident native communities more susceptible to invasion are those which, on average, have higher resource acquisition capacity, and lower drought resistance coupled with an apparently reduced water-use efficiency. We advocate the use of a mechanistic perspective in future research to comprehensively understand invasion dynamics, providing also new insights on the factors underlying community invasibility in different ecosystems.